1980
DOI: 10.3109/00365598009179555
|View full text |Cite
|
Sign up to set email alerts
|

Role of N-Acetyltransferase Phenotype in Human Susceptibility To Bladder Carcinogenic Arylamines

Abstract: N-acetyltransferase activity is species-specific and in animal experiments a determinant of the susceptibility of each species to arylamine bladder carcinogens. The effect of N-acetylation is that of inactivation. In humans, N-acetyltransferase activity is also genetically determined so that two N-acetyltransferase phenotypes exist, a rapid acetylator phenotype and a slow acetylator phenotype. N-acetyltransferase phenotype was determined in 71 bladder cancer patients and in 74 control subjects from Copenhagen.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 6 publications
0
13
0
1
Order By: Relevance
“…Many adverse drug and chemical reactions have been associated with acetylator status (Lunde et al, 1983;Drayer & Reidenberg, 1977;Wolf et al, 1980;Cartwright et al, 1982). It can therefore be of some importance in clinical and occupational settings to know the acetylator phenotype of individuals, and a number of screening methods using test drugs (such as isoniazid, sulphamethazine and dapsone) have been developed for this purpose (Evans, 1969;Schroder, 1972;Eidus & Hodgkin, 1973;Weber & Brenner, 1974;Carr et al, 1978;du Souich et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Many adverse drug and chemical reactions have been associated with acetylator status (Lunde et al, 1983;Drayer & Reidenberg, 1977;Wolf et al, 1980;Cartwright et al, 1982). It can therefore be of some importance in clinical and occupational settings to know the acetylator phenotype of individuals, and a number of screening methods using test drugs (such as isoniazid, sulphamethazine and dapsone) have been developed for this purpose (Evans, 1969;Schroder, 1972;Eidus & Hodgkin, 1973;Weber & Brenner, 1974;Carr et al, 1978;du Souich et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…In 1979, Lower et al [5] and Lower and Bryan [4] reported that slow acetylator phenotype had an increased bladder cancer risk in Sweden and Denmark, but it was not statistically signifi cant. However, certain published articles indicated no association between bladder cancer carcinogenesis and slow acetylator phenotype [4,5,[14][15][16][17][18][19][20][21] . On the other hand, Hanssen et al [23] and Roots et al [22] implied an elevated risk in slow acetylator phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotype gives the investigator a simpler classification system (rapid vs slow) than is easily achieved with a system of 15 or more alleles combined in many possible ways. The ability of NA T2 phenotype to predict risk has been shown in colon cancer and in bladder cancer (6,8,10,(39)(40)(41)(42)(43). Failure to identify an association with other diseases may be due to a lack of understanding of the mechanism of the disease and its link to NAT2.…”
Section: Discussionmentioning
confidence: 99%